European integration and the incompatibility of national varieties of capitalism: problems with institutional divergence in a monetary union - Johnston, Alison; Regan, Aidan (Köln, 2014)
"Recent literature on the European debt crisis emphasizes that rising external trade and lending imbalances between the European Monetary Union's (EMU) Northern and Southern member states served as a crucial determinant behind speculative divergence between these two regions. However, these gaping external imbalances only emerged with the launch of the single currency. In this paper, we examine how three different currency regimes – monetary union, fixed exchange rate, and flexible exchange rates – influence the mutual co-existence of export-led growth models (which predominate in the Eurozone's crisis-spared Northern economies) and domestic demand-led growth models (which predominate in the Eurozone's crisis-prone Southern economies). We hypothesize that external imbalances between these two growth models did not emerge prior to EMU because of the presence of two adjustment mechanisms in the real exchange rate: the nominal exchange rate (in soft currency regimes) and the promotion of inflation convergence by national central banks (in hard currency regimes). European monetary integration removed these two readjustment mechanisms, leading to a persistent divergence in the real exchange rate and ultimately to external imbalances between Europe’s diverse models of capitalism."